Helping students with autism spectrum disorder express their thoughts and knowledge in writing : tips and exercises for developing writing skills - Geither, Elise Joy Bonza; Meeks, Lisa (Jessica Kingsley Publishers, 2014)
Improving the writing skills of students with Autism Spectrum Disorder is an important factor in helping them to make a smooth transition from high school to the increased expectations of university. This book offers practical guidance and writing exercises for educators to use to help students to get their thoughts and knowledge down in writing.